(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article considers problems of the improvement of technical and tactical training of elite wrestlers in preparation for major international competitions. The paper analyzes various factors arising in the course of a competitive bout and gives recommendations for coaches.